Allogeneic Mesenchymal Stem Cell Therapy Promotes Osteoblastogenesis and Prevents Glucocorticoid‐Induced Osteoporosis. (30th June 2016) - Sui, Bingdong; Hu, Chenghu; Zhang, Xinyi; Zhao, Pan; He, Tao; Zhou, Cuihong; Qiu, Xinyu; Chen, Nan; Zhao, Xinyi; Jin, Yan
Abstract : To study the potential of mesenchymal stem cells (MSCs) without genetic manipulation to treat osteoporosis, the authors transplanted MSCs into mice with glucocorticoid‐induced murine osteoporosis. MSCs prevented the reduction of bone mass and strength. Donor bone marrow MSCs homed and inhabited recipient bone marrow for at least 4 weeks, prevented recipient bone marrow cell apoptosis, and induced recipient osteoblastogenesis. Abstract : Gene‐modified mesenchymal stem cell (MSC)‐like cells with enhanced bone marrow homing and osteogenesis have been used in treating glucocorticoid‐induced murine osteoporosis (GIOP). Recent preclinical studies have further demonstrated the immunomodulatory and anticatabolic potential of allogeneic MSCs in treating osteoporosis under inflammatory and autoimmune conditions. In this study, we investigated whether systemic infusion of allogeneic MSCs without genetic manipulation could prevent GIOP, whether anabolic and anticatabolic effects existed, and whether homing or immunomodulation underlay the putative therapeutic effects. Allogeneic bone marrow‐derived MSCs (BMMSCs) were isolated, identified, and systemically infused into mice treated with excessive dexamethasone. We revealed that allogeneic MSC transplantation prevented the reduction of bone mass and strength in GIOP. Bone histomorphometric analyses of bone remodeling demonstrated the maintenance of bone formation and osteoblast survival after MSC therapy. Using green fluorescent protein (GFP)‐labeled BMMSCs, we showed that donor BMMSCs GFP homed and inhabited recipient bone marrow for at least 4 weeks and prevented recipient bone marrow cell apoptosis, as shown by terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end labeling. Furthermore, donor BMMSCs GFP committed to Osterix (Osx) + osteoblast progenitors and induced recipient osteoblastogenesis, as exhibited by GFP‐Osx double‐labeling immunofluorescence analysis. No anticatabolic effects or systemic immunomodulatory effects of infused BMMSCs were detected. These findings demonstrated that allogeneic MSC therapy prevented GIOP by inhabiting and functioning in recipient bone marrow, which promoted osteoblastogenesis, which in turn maintained bone formation. Our findings provide important information regarding cell‐based anabolic therapy for GIOP and uncover MSC behaviors following the homing event. Significance: This study revealed the therapeutic potential of systemically infused, genetically unmodified allogeneic MSCs in glucocorticoid‐induced osteoporosis. The donor MSCs inhabited recipient bone marrow and promoted osteoblastogenesis. The therapeutic effects were based on maintenance of bone formation. These results provide important information regarding cell‐based anabolic therapy for glucocorticoid‐induced osteoporosis and uncover previously unrecognized mesenchymal stem cell behaviors following a homing event. The current study also indicates that minimizing the time of cell culture confers an advantage for increasing transplanted mesenchymal stem cells to the targeted organ to promote therapeutic effects.